Questioning the Location of the Old Kingdom Capital of Memphis, Egypt - Serena Love (Papers from the Institute of Archaeology, 2003)
The capital city of Memphis was ancient Egypt’s oldest and largest city. However, the city’s origin is shrouded in myth. This study challenges five different references to Memphis, from both classical and historical accounts and concludes that Memphis’ boundary should be redefined. These accounts are reviewed to illustrate the confusion amongst early historians and travellers as to the precise location of Memphis and to highlight the association between the capital and the pyramids of the Giza Plateau. For the Old Kingdom, the urban limits of Memphis should not be restricted to the modern mound of Mit Rahina, but rather the boundaries should be expanded to parallel the Old Kingdom pyramids. Recent archaeological investigations, employing sub-surface sampling techniques, have revealed contemporary Old Kingdom occupational debris scattered throughout the entire Memphite region. The inclusion of archaeological material, in combination with the historical records, will create a different interpretation for Egypt’s Old Kingdom capital city.
Keywords: sub-surface sampling; Memphis; Egypt